Checking in with the KU Leuven Fund for Fair Open Access - Verbeke, Demmy; Mesotten, Laura (Septentrio Conference Series, 2019)
KU Leuven has been supporting Green OA through its institutional repository Lirias for many years already. As it is clear, however, that Green OA provides only part of the solution for the crisis in scholarly communication, the university was looking to intensify its efforts to maximize exchange, collaboration and innovation thanks to the dissemination of scholarly results. This led to the establishment of the KU Leuven Fund for Fair Open Access in March 2018. This fund initially provided financial support for the production costs of OA monographs published by Leuven University Press as well as for the production costs of articles published in OA journals, on the condition that these journals are published according to the Fair OA model and maintain the highest academic standards. As of 2019, the scope of the fund was broadened to include financial support to non-commercial publishing initiatives and infrastructures in general. This poster briefly presents the KU Leuven Fund for Fair OA and details which articles, books, initiatives and infrastructures are supported during the first two years of operation. It also discusses the future of the fund and how it ties in with the open scholarship roadmap within KU Leuven.